Psychiatric comorbidity and order of condition onset among patients seeking treatment for chronic pain and opioid use disorder. (1st April 2021) - Barry, Declan T.; Beitel, Mark; Cutter, Christopher J.; Fiellin, David A.; Madden, Lynn M.; Lipkind, Nathan; Bollampally, Pooja; Liong, Christopher; Schottenfeld, Richard S.
Highlights: Order of onset for co-occurring chronic pain and opioid use disorder (OUD) varied. For most patients, chronic pain emerged before OUD. The Same Time group had the highest rates of co-occurring mood and anxiety disorders. The OUD First group had the highest rates of personality and substance use disorders. Abstract: Background: The study objective was to compare psychiatric comorbidity among patients seeking treatment for chronic pain and opioid use disorder (OUD) by order of condition onset (i.e., "Pain First, " "OUD First, " "Same Time"). Methods: Data from 170 patients entering two clinical trials of treatments for current comorbid chronic pain and OUD conducted between March 2009 and July 2013 were compared by order of condition onset. The Structured Clinical Interview for DSM-IV-TR Axis I Disorders and the Diagnostic Interview for DSM-IV Personality Disorders (Axis II) were performed by doctoral-level providers using a standardized training protocol. Age of onset group differences on specific diagnostic variables were examined using multinomial logistic regression. Results: Fifty-two percent were in the "Pain First" group (n = 89), 35 % in the "OUD First" group (n = 59), and 13 % in the "Same Time" group (n = 22). Compared with the Pain First group, the Same Time group was less likely to report heroin (vs. prescription opioids) as the primary drug used (OR = 0.20, 95 % CI = 0.06−0.72) or meet criteria for an Axis II disorder (OR = 0.24, 95 % CI = 0.07−0.83). Compared with the Pain First group, the OUD First group was more likely to meet criteria for a current nonopioid substance use disorder (OR = 3.20, 95 % CI = 1.22−8.40). Conclusions: Our findings regarding differences in psychiatric comorbidity associated with order of condition onset indicate that varying pathways may exist for the emergence of chronic pain and OUD; further research should investigate potential treatment implications.